Catch Uncertainty and Reward Schemes in a Commons Dilemma: An Experimental Study (2019)
We design and conduct a laboratory experiment with students and a field experiment with fishermen to test how catch uncertainty and reward schemes affect extraction in an open access fishery. We find that uncertainty in the relationship between effort and catch increases extraction effort and accelerates resource depletion. Importantly, participants increase their extraction after a disadvantageous shock, but do not react to advantageous shocks. One possible explanation of this phenomenon is a self-serving bias. Price-responsive demand, relative to a fixed price setting, decreases extraction effort and increases efficiency. Price-responsive demand has a greater effect on students than on fishermen living inside a marine protected area, but fishermen outside this restricted area are very responsive to conditional pricing. © 2018, Springer Science+Business Media B.V., part of Springer Nature.